Increased Epileptiform EEG Activity and Decreased Seizure Threshold in Arctic APP Transgenic Mouse Model of Alzheimer’s Disease - Ziyatdinova, Sofya; Rönnbäck, Annica; Gurevicius, Kestutis; Miszczuk, Diana; Graff, Caroline; Winblad, Bengt; Pitkänen, Asla; Tanila, Heikki (Current Alzheimer Research, 2016)
Several Alzheimer model mice carrying transgenic amyloid precursor protein (APP) with the Swedish mutation have been reported to exhibit spontaneous seizures and/or increased epileptiform EEG activity. The primary cause for the epilepsy phenotype is still under debate. In contrast to mice with APPswe mutation that develop extracellular amyloid plaques, mice with APP Arctic mutation (E693G) have no bias toward β-secretase cleavage and display intracellular amyloid deposits but not plaques. We conducted a systematic long-term video-EEG recording in three two-week sessions on 21 APParc and 11 wild-type control mice between 3.5 and 8 months of age. Spontaneous seizures were not detected more often in APParc mice than in their wild-type control mice. Long (1 – 5 s) epileptiform discharges were occasionally detected in both APParc and wild-type mice, but short (0.5 – <1 s) epileptiform discharges were more common in APParc mice than in wild-types. However, they were far less frequent than in 6 APPswe/PS1dE9 mice recorded in parallel. In pentylenetetrazole test for seizure susceptibility, APParc mice displayed a shorter latency to sharp-wave discharges than wildtype mice but no increase in seizure duration. These data speak for a relatively mild epilepsy phenotype in APParc mice compared to APPswe mice despite even higher extent of APP overexpression. Thus extracellular amyloid plaques or increased β-secretase cleavage products appear important for the epilepsy phenotype in APPswe mice.
Keywords: pentylenetetrazole